CLINICAL AND INSTRUMENTAL DATA COMPLEX AGGREGATIVE IN FATAL OUTCOME RISK PROGNOSIS IN NEWBORN WITN CONGENITAL HEART DISEASES - Елена Глебовна Цой; Людмила Николаевна Игишева; Ольга Владимировна Куренкова; Сергей Алексеевич Максимов; Любовь Михайловна Казакова (The Publishing House Medicine and Enlightenment, 2017)
Tactical issues of newborn monitoring optimization with congenital heart diseases require a decision. Objective - a predicative model creation of high fatal outcome risk in newborn with congenital heart disease in neonatal period, a received model approbation in practices. Materials and methods. Clinical and instrumental data analyzing was carried out in 98 newborn with critical congenital heart diseases on the third day of life. 45 criteria were outlined among all clinical and instrumental data, each of them was a fatal outcome predictor in the present patients category. A predicative model of high fatal outcome risk was created with the aid of «trees classification» statistics method. The present algorithm was approbated in 23 newborn with congenital heart disease. Results. A combination of fatal outcome risk factors in neonatal period with congenital heart disease was carried out. Hypoxemia with saturation below 79%, the heartbeat rate below 119/min, circulation minute volume more than 720 l/min, stroke output below 5,3 ml, myocardial mass below 7,1 gr or above 13,7 gr. Created predicative model had a diagnostic effectiveness - 92,9%. Diagnostic effectiveness was 87,0% during the approbation and a strong connection between risk factors and an outcome was shown as well. Conclusion. Arterial oxygen saturation level, heartbeat rate, echocardiographic data: stroke output, left ventricular myocardial mass, circulation minute volume should be included inti the predicative algorithm of a negative outcome in patients with critical congenital heart disease.